A Correlative Study Between Haematological and Biochemical Parameters in Hepatitis B - Ali, Susan Jameel (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2019)
Hepatitis-B (HBV) is a viral disease cause liver damage, cirrhosis, fibrosis and hepatocellular carcinoma. Present study attempted to elucidate the biochemical and haematological markers other than Australia antigen, of hepatitis,B,vairusV (HBsAg) for better assessment of HBV infection. The present study was conducted on 76 men, 50 of them were found to be HBeAg positive and 26 were negative, mean age was53Â±5.7years. Haematological parameters such as Absolute Erythrocyte( Abs Eryt), Absolute Leukocyte(Abs Leuk) , Haemoglobin(Hb), Packed Cell Volume(PCV),Mean Corpuscular Volume (MCV), Red Cell Distribution Width (RDW), Mean Corpuscular Haemoglobin (MCH),MCH Concentration(MCHC) ,Neutrophils(Neut) ,Lymphocyte(Lymph), Monocyte(Mono), Eosinophil(Eosin) , Basophil (Baso) , Absolut platelet(Abs.Plt), Red Blood Distribution(RBD)and biochemical markers such as Alanine aminotransferase(ALT), Aspartate aminotransferase(AST), Alkaline phosphatase(ALP), Gamma glutamyl transpeptidase(GGT), Total Bilirubin (T.Bil), Albumin(Alb), C- reactive protein (CRP), Amylase(Amy), Creatinine(Crea), Sodium(Na) , Potassium(K), were estimated for HBV patients and healthy groups.Statically at (Pâ‰¤ 0.05) Abs Plt was highly significant elevated, Hb, Abs Leuk, Neut%, Lymph% and Eosin% were significant increases while other haematological parameters showed no differences in HBV patients compared with controls. Liver enzymes (ALT, AST, GGT) and T.Bil were highly significant increased, Alb , CRP and Amyl were moderately increased, niether Crea, Na nor K levels have differences in HBV patients compared with controls.ALT has strong positive correlation with Leuk and with Abs Plt in HBV patients. liver enzymes ALT, AST, ALP, GGT, T.Bil and Abs Plt can be used as monitoring markers with the strong correlation between ALT and Abs Plt as an assessment tools for HBV infection.